Implementasi Balanced Scorecard Dalam Meningkatkan Kinerja Lembaga Pendidikan - Maryati Maryati; Iim Wasliman; Deti Rostini; Yosal Iriantara (Indonesian Journal of Learning Education and Counseling, 2022)
Research is based on the problem of weak educational institutions to display achievements amid the level of competitive competition, relevant, strategy, effective, efficient, productive is very necessary. It’s Analyzes the implementation of BSC in improving the performance of Darul Hikam Foundation and BPI Foundation in Bandung City. Grand Theory is Kaplan and Norton's performance theory, where BSC is a method of comprehensively measuring performance not only limited to financial performance but extends to non-financial performance. The results showed that the Proses preparation of  BSC educational institutions has not been fully implemented, starting from the preparatory stage,  stakeholders involved, reasons in improving the performance of educational institutions, resources, and measures in the preparation of BSC; The BSC concept of several indicators have not been implemented by the description of the BSC concept of the education sector, which includes vision, mission, SWOT analysis, BSC perspective, strategic objectives, strategy map, and Key Performance Indicators (IKU); Implementation of  BSC has not been done well, including socialization, pilot project system, special teams, information and technology (IT), BSC consultants, and steps to implement BSC; The problems facing educational institutions. Educational institutions always strive to prepare a variety of needs to implement BSC, find solutions in dealing with every problem, as well as various obstacles that occur by taking strategic steps; Where to implement BSC if done gradually and arrange will improve the performance of educational institutions.   Abstrak. Penelitian dilatarbelakangi permasalahan lemahnya lembaga pendidikan untuk menampilkan prestasi ditengah tingkat persaingan kompetitif, hingga strategi yang relevan, efektif, efisien, produktif sangat diperlukan. Peneliti menganalisis implementasi BSC dalam meningkatkan kinerja Yayasan Darul Hikam dan Yayasan BPI Kota Bandung. Grand Theory-nya yaitu teori kinerja Kaplan dan Norton, dimana BSC merupakan metode untuk mengukur kinerja secara komprehensif tidak hanya terbatas pada kinerja keuangan, namun meluas pada kinerja non-keuangan. Hasil penelitian menunjukkan bahwa Proses penyusunan BSC lembaga pendidikan belum sepenuhnya dilaksanakan, mulai dari tahap persiapan, stakeholders yang terlibat, ragam alasan dalam meningkatkan kinerja lembaga pendidikan, sumber daya, dan langkah-langkah dalam penyusunan BSC; Penjabaran konsep BSC beberapa indikator belum dilaksanakan sesuai dengan penjabaran konsep BSC sektor pendidikan, yang meliputi visi, misi, analisis SWOT, perspektif BSC, tujuan strategis, peta strategi (strategy map), dan Indikator Kinerja Utama (IKU); Implementasi BSC belum dilakukan dengan baik, meliputi sosialisasi, sistem pilot project, tim khusus, informasi dan teknologi (IT), konsultan BSC, dan langkah-langkah menerapkan BSC; Masalah-masalah yang dihadapi lembaga pendidikan. Lembaga pendidikan selalu berusaha untuk mempersiapkan ragam kebutuhan untuk mengimplementasikan BSC, mencari solusi dalam menghadapi setiap permasalahan, serta berbagai kendala yang terjadi dengan melakukan langkah-langkah strategis; Dimana implementasi BSC jika dilakukan secara bertahap dan runtut akan meningkatkan kinerja lembaga pendidikan.